Baseline Survey of New Medical Undergraduates: Profile and Potential for Follow-Up - De Abrew, A.; Karunathilake, I.M.; Perera, J. (South-East Asian Journal of Medical Education, 2017)
Background: The Faculty of Medicine, University of Colombo is one of the foremost institutes providing Medical Education in Sri Lanka. Many factors affect academic performance of medical undergraduates, including admission scores, personality, gender, English language ability, coping skills and availability of academic and social support. Objectives: To profile and quantify selected factors that may predict academic performance among medical undergraduates. Methods: A descriptive cross-sectional study was carried out on new entrants. A structured self-administered questionnaire collected data on demographic characteristics, previous academic performance, extra-curricular activities, residence and travel, English and Information Technology (IT) competency. Results: Details were obtained of 198 students, including 8 (4%) foreign students. Average age was 22.1 years with a female preponderance of 55%. Most (63%, n=124) had entered at the first attempt, with all enrolments on merit. While over one third (n=72) entered from the Colombo District, only 44 were permanent residents. Participation in extra-curricular activities was reported by 42%. Most (n=117) had obtained an “A” grade at the General English examination, and reported average to high English language competency. However, only 34 (17%) reported high competence in listening comprehension. Almost all (99.5%) had a mobile phone and most reported familiarity with simple IT based tasks. Conclusions: New entrants demonstrate high rates of conventionally recognised predictors of academic success such as entry at first attempt, female gender and English proficiency. There is a need to explore the use of these and other non-cognitive factors to identify students who may be at risk of poor academic performance and offer early remedial intervention.
Keywords: Medical Students; Medical Education; Sri Lanka